Age-dependent stress response DNA demethylation and gene upregulation accompany nuclear and skeletal muscle remodeling following acute resistance-type exercise in rats - Erik P. Rader; Brent A. Baker (Canadian Science Publishing, 2020)
Efficacy of high-intensity resistance exercise becomes progressively compromised with aging. Previously, to investigate this, we developed a rodent model of high-intensity training consisting of stretch-shortening contractions (SSCs) and determined that following one month of training, young rats exhibit a robust stress response and 20% performance increase, whereas old rats display a muted stress response and 30% performance decrease. Whether these age-specific responses occur early in training and constitute primary factors in adaptation/maladaptation was not addressed. The aim of the present study was to characterize performance, remodeling, and stress response transcriptional profile 6-120 h following acute SSC exposure. For young rats, the stress response pathway was highly regulated (≥20 differentially expressed genes at each time point) and was accompanied by robust DNA demethylation, tissue remodeling, and isometric torque recovery. For old rats, a muted transcriptional profile (13 and 2 differentially expressed genes at 6 and 120 h, respectively) coincided with deficiencies in demethylation, muscle remodeling, and torque recovery. These findings occurred in the context of heightened chronic levels of stress response gene expression with aging. This demonstrates that age-related constitutive elevations in stress response gene expression was accompanied by diminished SSC-induced responsiveness in epigenomic regulation and tissue remodeling.